ChemInform Abstract: Synthesis of Multisubstituted Cyclobutenones via Copper‐Catalyzed Intramolecular C‐Vinylation of Ketones. Issue 44 (15th October 2015) - Zhu, Lin; Li, Chaozhong
Abstract A novel facile method is developed for the intramolecular cyclization of vinyl bromides (I) and (III) to form tetrasubstituted cyclobutenones in high yields.